2003
DOI: 10.1007/s005950300074
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations of Neurofibromatosis Type 1 Gene in Small Cell Lung Cancers

Abstract: A mutation in this region could imply a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Why, for example, are NF1 patients not predisposed to lung tumours given that at least 10% of all sporadic lung cancers have NF1 mutations [8, 65, 72, 166]?…”
Section: Main Bodymentioning
confidence: 99%
“…Why, for example, are NF1 patients not predisposed to lung tumours given that at least 10% of all sporadic lung cancers have NF1 mutations [8, 65, 72, 166]?…”
Section: Main Bodymentioning
confidence: 99%
“…NF1 plays the role of a tumor suppressor protein by inhibiting RAS. Mutations in NF1 have been reported in both NSCLC and small cell lung cancer [61,118,119]. It is possible that NF1 plays an important role in the pathogenesis of SQCC given that it is required for the normal development of epidermal cells.…”
Section: Nf1mentioning
confidence: 99%
“…In a separate study, Furukawa et al analyzed 37 patients with primary lung cancer and identified NF1 mutations in three patients, all of which had small cell lung carcinoma. All three mutations identified were located in the GTPase-activating protein (GAP)-related domain (GRD) close to the mutational hot spot within exon 24 [231]. Li et al have reported three cases of adenocarcinoma of the colon, myelodysplastic syndrome, and anaplastic astrocytoma, which also had NF1 mutations involving the GRD domain [232].…”
Section: Somatic Nf1 Mutationsmentioning
confidence: 99%